Effect of grain size on stress induced martensitic transformations in a Cu–Al–Be polycrystalline shape-memory alloy. Pseudoelastic cycling effects and microstructural modifications - Sade Lichtmann, Marcos Leonel (2014)
Grain size has a strong effect on the pseudoelastic properties of shape-memory alloys. Different grain sizes and several related phenomena are studied. This involves the dependence of the transformation and retransformation stresses on grain size and on the amount of transformed material. A pronounced drop of transformation stresses on cycling is observed, until an asymptotic behavior is reached. This is related to the creation of defects (dislocations and dislocation arrays) and microplates of martensite, which are the defects necessary to allow the grains to accommodate due to the shape change imposed by the martensitic transformation. The asymptotic hysteresis is related to the internal work for the grains to accommodate each other once the necessary defects were created. The asymptotic hysteresis increases linearly as the grain size decreases. A simple model shows that the slope is related to the (d/e) ratio, where d is the average grain size and e is the width of the specimen. This effect arises from the presence of the free surfaces that release the plastic work for grain accommodation.